Beyond Compliance: Unpacking the Disconnect between Instructional Leadership and Enacted Curriculum Competence in the Classroom - Jaja Sudarjat; Parid Abdulloh; Julie Simon Macariola (Journal of Pedagogy and Education Science, 2026)
This study examines the influence of principal supervision and teacher curriculum competence on learning effectiveness, with teaching quality serving as a mediating variable. The study aims to analyze the direct relationships among the variables and to examine the mediating role of teaching quality in improving learning effectiveness. A quantitative explanatory survey design was employed. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The measurement model demonstrated satisfactory validity and reliability, with outer loadings exceeding 0.70, Cronbach's Alpha ranging from 0.883 to 0.889, Composite Reliability from 0.923 to 0.931, and AVE from 0.718 to 0.761. The structural model revealed that all proposed hypotheses were supported. Principal supervision positively affected teaching quality (β = 0.428, p < 0.001) and learning effectiveness (β = 0.238, p = 0.005), while teacher curriculum competence positively influenced teaching quality (β = 0.456, p < 0.001) and learning effectiveness (β = 0.257, p = 0.003). Teaching quality also exerted a significant positive effect on learning effectiveness (β = 0.396, p < 0.001). The model explained 61.2% of the variance in teaching quality and 67.3% of the variance in learning effectiveness. The findings highlight teaching quality as the key mechanism linking principal supervision and teacher curriculum competence to enhanced learning effectiveness, offering both theoretical and practical contributions to educational management.